Comparative systems of assessment of illness or disability for the purposes of adult social welfare payments, First Report (Final) (Incapacity for Work) - Cousins, Mel; Roberts, Simon; Stafford, Bruce (Mel Cousins & Associates, 2016)
This is the first report of the study of comparative systems of assessment of illness or disability for the purposes of adult ‘incapacity’ social welfare payments. The purpose of the research is to examine systems for medical/disability assessment and review used in other comparable jurisdictions for assessing entitlement to social welfare illness and disability payments, and to draw key learning for the Irish system.